PENGARUH SISTEM PENGENDALIAN MANAJEMEN, PROFITABILITAS DAN PERTUMBUHAN LABA TERHADAP KINERJA MANAJERIAL PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Rini Wahyuni Hutasoit; Haervi Yunira (Jurnal Widya, 2024)
This research aims to determine the effect of management control systems, profitability and profit growth on managerial performance in the food and beverage sub-sector listed on the Indonesian Stock Exchange. The type of research used in this research uses quantitative research. The data source used in this research uses secondary data sources. The number of samples in this research was 80 research samples. The results of this research show that the internal control system (X1) and profit growth (X3) have a positive and significant effect on managerial performance (Y), while profitability (X2) does not have a positive and significant effect on managerial performance (Y) in the food and beverage sub-sector. Drink. Simultaneously, the management control system variables, profitability and profit growth influence managerial performance